2022
DOI: 10.1007/s12281-022-00441-1
|View full text |Cite
|
Sign up to set email alerts
|

Updates on Histoplasmosis in Solid Organ Transplantation

Abstract: Purpose of Review Histoplasmosis remains a challenging infection in solid organ transplantation. This review provides a topic update with emphasis on the changing Histoplasma epidemiology, along with new diagnostic and treatment innovations. Recent Findings Recent years have observed expanding Histoplasma geographic distribution due to climate change, environmental disruption, and host factors. Early clinical experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 87 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Using a weighted analysis of three environmental soil characteristics measured across the continental United States, Maiga et al showed that the soils suitable for growth of histoplasmosis have expanded into the upper Missouri River Basin, with pockets of suitability in almost all states [15]. Transplant-associated histoplasmosis can occur as a de novo infection from environmental exposures, as a donor-derived infection or as reactivation from a latent infection, though the latter remains controversial [37]. In a prior autopsy series in which calcified granulomas were examined, two thirds had yeast forms consistent with Histoplasma spp.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a weighted analysis of three environmental soil characteristics measured across the continental United States, Maiga et al showed that the soils suitable for growth of histoplasmosis have expanded into the upper Missouri River Basin, with pockets of suitability in almost all states [15]. Transplant-associated histoplasmosis can occur as a de novo infection from environmental exposures, as a donor-derived infection or as reactivation from a latent infection, though the latter remains controversial [37]. In a prior autopsy series in which calcified granulomas were examined, two thirds had yeast forms consistent with Histoplasma spp.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Liposomal amphotericin B is associated with less toxicity and mortality and is considered the agent of choice for induction therapy in patients with severe disease [96]. The American Society of Transplantation Infectious Diseases Community of Practice recommends continuation of induction therapy for a minimum of 1 to 2 weeks with clinical evidence of improvement [37]. In patients with CNS involvement, longer courses of induction therapy are recommended (i.e., 4 to 6 weeks) [37,97].…”
Section: Managementmentioning
confidence: 99%
“…Transplant-associated histoplasmosis can occur as a de-novo infection from an environmental exposure, as the reactivation of a latent infection or as a donor-derived transmission [ 95 ]. Most of the cases occur within the first 2 years following transplantation, though the median time from transplantation varies among the different studies [ 92 , 94 , 95 , 96 ]. Donor-derived histoplasmosis may occur in 1:10,000 transplants and is characterized by occurring in the early post-transplant period [ 83 ].…”
Section: Special Populationsmentioning
confidence: 99%
“…Solid organ transplant (SOT) recipients and other immunocompromised hosts have a propensity for severe infection, inclusive of extrapulmonary and disseminated disease. The infections in SOT recipients are best categorized as mild, moderate, or severe [35].…”
Section: Histoplasmosis In Solid Organ Transplant Recipientsmentioning
confidence: 99%
“…Irrespective of initial disease severity, antifungal therapy should be continued for a minimum of 12 months or more in patients necessitating continued high-level immunosuppression after a relapsed disease or in CNS involvement. Fluconazole (FCZ) or newer-generation azoles, including voriconazole (VCZ), isavuconazole (ISZ), and posaconazole (PCZ), has been used as an alternative in patients with ITZ intolerance [35]. Once the diagnosis of histoplasmosis is made, immunosuppressive medication should be reduced, although the optimal timing and strategy in this regard are unknown [36].…”
Section: Histoplasmosis In Solid Organ Transplant Recipientsmentioning
confidence: 99%